2014
DOI: 10.1371/journal.pcbi.1003616
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Length and Variance of the Eukaryotic Cell Cycle Phases by a Stochastic Model and Dual Nucleoside Pulse Labelling

Abstract: A fundamental property of cell populations is their growth rate as well as the time needed for cell division and its variance. The eukaryotic cell cycle progresses in an ordered sequence through the phases and and is regulated by environmental cues and by intracellular checkpoints. Reflecting this regulatory complexity, the length of each phase varies considerably in different kinds of cells but also among genetically and morphologically indistinguishable cells. This article addresses the question of how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 41 publications
2
68
0
1
Order By: Relevance
“…In human cells, this process typically lasts 8–10 hours 1 . Different regions of the genome replicate at different times during S phase, following a defined replication timing (RT) program 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In human cells, this process typically lasts 8–10 hours 1 . Different regions of the genome replicate at different times during S phase, following a defined replication timing (RT) program 28 .…”
Section: Introductionmentioning
confidence: 99%
“…These apparently stochastic differences in cell-cycle durations were originally attributed exclusively to the G1 phase 13 . However, more recent studies in multiple cell types have revealed that S and G2 also contribute significant variability to total cell cycle duration 3,14,15 . Collectively, these studies have revealed that differences in cell cycle durations are an inherent property of individual cells and raise the fundamental question of how these durations are determined.Over the past 50 years, multiple models have been put forth to explain the differences in cell cycle phase durations among individual cells.…”
mentioning
confidence: 99%
“…To infer cell cycle kinetics from our data we implemented a non-spatial model of dividing NSCs with 5 parameters: the minimal cell cycle length d cc and minimal S-phase length d sp , their variability β cc and β sp parametrizing a lag-exponential (Weber et al, 2014) distribution, and the re-division probability p re-div (see Supplementary Figure 5A). From this model we simulate dividing NSCs and a BrdU-EdU-labelling experiment (Supplementary Figure 5B) and evaluate the percentage of re-dividing cells and DLS.…”
Section: An Agent Based Model Of Re-dividing Nscs Recreates Aggregatementioning
confidence: 99%
“…32h+9h is however not able to explain a plateauing of reviding NSCs for ∆t ≥ 24h. Instead of constant cell cycle and S-phase length, we thus assume them to be distributed as delayed exponential distributions (Weber et al, 2014) ,…”
Section: Cell Division Modelmentioning
confidence: 99%